Qualitative Evaluation of Antibiotics Use for Ventilator Associated Pneummonia (VAP) Patient in ICU Dharmais Cancer Hospital Using Gyssens Method - Ramadhanti, Shahyawidya; Radji, Maksum; Andalusia, Rizka (Universitas Padjadjaran, 2023)
Ventilator-associated pneumonia (VAP) is a pulmonary infection that occurs after more than 48 hours of mechanical ventilation or endotracheal intubation. VAP is the most common nosocomial infection in ICU (Intensive Care Unit), and of course the use of antibiotics will affect the treatment of the infection. This study aims to evaluate the quality of antibiotic use for VAP treatment in ICU Dharmais Cancer Hospital using Gyssens method, evaluate the different outcomes of antibiotic therapy that are rational and irrational according to the Gyssens method, and evaluating the distribution of rational (category 0) and irrational (category 1-5) antibiotic use. This prospective study was carried out from February to May 2017 with descriptive analyses. Antibiotic uses were documented prospectively by a pharmacist and analysis by using Gyssens method. Pharmacist was used total sampling method, which is included all adult VAP patients in ICU. A total of 29 patients (18,24%) were reviewed from 159 patients. The most dominant antibiotic use for VAP empiric treatment was meropenem and the most dominant antibiotic use for VAP definitive treatment was levofloxacin. Factors affecting the quality of antibiotic use include type of the therapy, number of antibiotics used by patient and length of stay (P>0,05). Factors affecting the therapy outcome of VAP patient was time of antibiotic use (P<0.05). The relationship between outcome therapy and quality of antibiotic use based on Gyssens method shows on category 0 which died 64,3%, category 2 died 66,7% and the category 4 died 75%. The relationship between outcome therapy and quality of antibiotic use based on Gyssens method shows more irrational use of antibiotics then the therapy outcome is not getting better.